PENGARUH METODE PEMBELAJARAN ROLE PLAYING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP IPA PADA SISWA KELAS IV SEKOLAH DASAR NEGERI 101770 KECAMATAN MEDAN TEMBUNG - Joya Situmorang; Wildansyah Lubis; Fahrur Rozi; Winara; Tiarnita Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of the Role Playing learning method on the science concept understanding of fourth-grade students at SD Negeri 101770 Medan Tembung District. This research employed a quantitative approach using a Quasi-Experimental method with a Nonequivalent Control Group Design. The population consisted of all fourth-grade students at SD Negeri 101770 Medan Tembung District. The sample comprised two classes: Class IV-A as the experimental group and Class IV-B as the control group, with a total sample of 30 students. Data were collected through pretests and posttests using an instrument that had been tested for validity, reliability, item difficulty, and discrimination index. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene's Test for homogeneity, and the Independent Samples t-test for hypothesis testing. The results showed that the science concept understanding of students in the experimental group was better than that of students in the control group. The hypothesis test yielded a significance value (Sig. 2-tailed) of less than 0.05, indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. These findings indicate that the Role Playing learning method has a significant effect on the science concept understanding of fourth-grade students at SD Negeri 101770 Medan Tembung District. Therefore, the Role Playing learning method can be used as an effective alternative instructional strategy to improve students' science concept understanding.